Low-temperature CO2 reforming of methane over Ni supported on ZnAl mixed metal oxides. (13th April 2017) - Sokolov, Sergey; Radnik, Jörg; Schneider, Matthias; Rodemerck, Uwe
Abstract: Ni catalysts supported on mixed ZnOAl2 O3 and on pure ZnO and Al2 O3 were prepared, characterized by XRD, TPR, and XPS, and tested in long-term methane dry reforming at low temperature (400 °C). Depending on Zn/Al ratio in the supports, the catalysts varied in their physico-chemical properties and exhibited different trends in their on-stream catalytic activity. Catalysts with high alumina content consist of a mixture of alumina and zinc aluminate phases with metallic Ni particles on their surface. These samples show medium activity for reforming and high on-stream stability. The catalysts on mixed Zn-rich supports were more active than those on Al-rich supports and exhibited maxima in their activity after 30–40 h on stream, while Ni on pure ZnO possessed very low activity. Such contrast in performance of Zn-rich catalysts was explained by detected transformation of initially formed NiZn alloy to a mixture of Ni and Ni3 ZnC0.7 particles that are assumed to have higher activity for reforming. Moreover, the size of Ni-containing particles on Zn-rich supports decreased under reaction conditions resulting in higher Ni dispersion. Graphical abstract: Highlights: Ni catalysts supported on mixed ZnOAl2 O3 were tested for dry reforming of methane. ZnO:Al2 O3 ratio influences to a great extent catalytic performance. Ni on Al2 O3 -rich supports carries Ni on zinc aluminate phase and show high stability. ZnO-rich catalysts possess NiZn alloy particles on their surface. The latter are in situ transformed to Ni and Ni3 ZnC0.7 particles.